REMOTE CONTROLLED FERTILIZER SPRAY DRONE - Nayak, Niranjan; Kumar Sahoo, Bijay; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The farming sector is the biggest sector of India it comprises around 60% of all sector, as compare to its size the technologies which are developed for improving the condition of farmer and to increase the production of a farm are very less. So, in this paper a drone is discussed which is capable of spraying the fertilizer on field. The Drone helps the farm owners for spraying fertilizer on farm land efficiently and effectively. The drone comprises several units the first unit is communication unit comprises radio a transmitter and receiver for controlling, a microcontroller and sensors for processing and compiling user commands. A spray unit for spraying fertilizer on crops.